Recognising the potential role of native ponies in conservation management. (July 2019) - Fraser, M.D.; Stanley, C.R.; Hegarty, M.J.
Abstract: Population control of feral horses has been the subject of public debate in many parts of the world in recent years due to wide-reaching ecological and societal impacts. However, the feral populations in these high-profile cases are not 'native' but are instead descended from animals which escaped from or were released by settlers. This paper considers i) the potential role of indigenous equids as conservation grazers within native ecosystems currently in poor condition, and ii) the value of supporting semi-wild native ponies specifically. We argue that the high ecological overlap between ponies and cattle reported in a range of studies means that they should be considered as alternative tools for conservation management, particularly in scenarios where there is a need to reduce the dominance of plant species avoided by more-selective small ruminants such as sheep. Semi-wild ponies could be particularly suited to conservation grazing because their genomes have been predominately shaped by natural and not artificial selection, meaning they may have adaptations no longer present in domesticated equids. With agricultural and environmental policy in the EU and UK under major review, it is anticipated that the wider delivery of public goods, rather than primary production, will be prioritised under future subsidy payment schemes. Recognising the value of native ponies as conservation grazers would broaden the range of routes by which land managers could achieve biodiversity gain, whilst simultaneously supporting at-risk equine genotypes. Highlights: There is high dietary overlap between ponies and cattle. Ponies should be considered as alternative tools for conservation management. Semi-wild ponies' genomes have been shaped by natural and not artificial selection. Conservation grazing could provide a sink for excess animals from semi-wild herds.